An Audit of Operative Notes at TUTH - Shah, S; Dangol, B; Kumari, S; Guragain, RP (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 25-26 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6802